The Diversity of Audience Responses on Book Review Platforms (Goodreads and Abjjad as a Case Study) - Al-Adhba, Sita (El Omda in Linguistics and Discourse Analysis, 2019)
Abstract: This research paper focuses on the variety of responses among those who peruse the checking books websites on the internet, especially novels. It includes many different aspects, some of them include the contexts of several novels whether they are cultural, social, political or religious novels. Some of them are related to characters, language, narration, plot and others are related to some aspect of a certain novel. All these responses showed the flexibility of the websites, their openness and ability to be divided into hyperlinks and the transfer of responses to deeper and wide spread stages. Also using computers gave more freedom to express and show opinions. Studying these responses was carried out through choosing examples representing these responses such as: "Bamboo Trunk" by Saoud Al Sanoussi on Goodreads website and "The Children of our Lane" by Naguib Mahfouz on Abjad website.